2017
DOI: 10.1037/cbs0000086
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the validity and reliability of the French version of the Brief Self-Control Scale.

Abstract: This study aims to develop and to validate a French version of the Brief Self-Control Scale (BSCS; Tangney et al., 2004). This instrument is usually applied as a unidimensional self-report measure for assessing trait self-control, which captures one’s dispositional ability to resist short-term temptation in order to reach more valuable long-term goals. Data were collected from two independent samples of French-speaking individuals (n1 = 287; n2 = 160). Results indicated that the French version of the BSCS can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 78 publications
0
27
0
5
Order By: Relevance
“…Considerando este resultado, se analizó el nivel de asociación que existía entre las dos dimensiones propuestas por Maloney et al (2012) y se encontró que entre ellas existía una correlación de Pearson igual a -.81. Este grado de correlación y su direccionalidad en sentido negativo, a la luz de los criterios de interpretación propuestos en la literatura (Bentler, 2006), indican que estos factores permiten medir dos dimensiones diferenciadas entre sí, pero que se encuentran contenidas por un factor de orden superior que podría ser denominado, siguiendo con la nomenclatura utilizada por los creadores de la BSCS, como autocontrol.…”
Section: Discussionunclassified
“…Considerando este resultado, se analizó el nivel de asociación que existía entre las dos dimensiones propuestas por Maloney et al (2012) y se encontró que entre ellas existía una correlación de Pearson igual a -.81. Este grado de correlación y su direccionalidad en sentido negativo, a la luz de los criterios de interpretación propuestos en la literatura (Bentler, 2006), indican que estos factores permiten medir dos dimensiones diferenciadas entre sí, pero que se encuentran contenidas por un factor de orden superior que podría ser denominado, siguiendo con la nomenclatura utilizada por los creadores de la BSCS, como autocontrol.…”
Section: Discussionunclassified
“…According to Tangney et al (2004) the internal consistency estimates (alpha) were 0.83 and 0.85, and the test-retest reliability estimate over a three-week interval was 0.87. Later research has confirmed relatively high reliability and test-retest stability in other samples (Malouf et al, 2014), and using other translations of the test (Brevers, Foucart, Verbanck, & Turel, 2017;Nebioglu, Eroglu, & Konuk, 2012;Unger, Bi, Xiao, & Ybarra, 2016). This brief form consists of thirteen questions, such as: 'I am good at resisting temptation.'…”
Section: Trait Self-controlmentioning
confidence: 97%
“…Since its publication, this brief measure has been used in more than 100 published studies with diverse and heterogeneous samples, and its utility has been demonstrated for assessing trait self-control and for predicting a variety of behavioral outcomes [12]. Additionally, several linguistic adaptations of the BSCS have been developed, including French [13], Chinese [14], Turkish [15], and German versions [16]. Nonetheless, an Italian version has yet to be developed and validated and hence, the present study aims to develop and test the the psychometric properties of an Italian version of the BSCS.…”
Section: Introductionmentioning
confidence: 99%